Biodegradable Hydroxyethyl Cellulose (HEC)-Chitosan (CS)-Lemon Peel Composite Films: A Sustainable Alternative to Synthetic Food Packaging - Kotancilar, Sena Karin; Gerigitmez, Yaren; Akin, Zeynep sude; Senturk, Kubra; Ozekmekci, Mehtap (Wiley, 2025)
The presence of petroleum-based polymers in food packaging is detrimental to the environment, and biodegradable films from dried lemon peel powder (LMP) were developed as a sustainable alternative. The films were prepared by incorporating 1- to 4-wt% LMP into a solution of hydroxyethyl cellulose (HEC) and chitosan (CS) using a solvent casting method. Lemon peel powder was analysed for its components including phenol, lipid, lignin, flavonoid, pectin and ash content. The physicochemical, mechanical and functional properties of the films were investigated. According to Fourier transform infrared spectroscopy, the interaction between the lemon peel and the polymer matrix was confirmed. As the amount of lemon peel powder increased, the film became more hydrophilic and its water solubility, thickness and vapour permeability increased. The contact angle value for HEC-CS and HEC-CS-LMP4 films slightly decreased from 88.39 degrees to 54.39 degrees, respectively. The tensile strength decreased from 107.30 +/- 0.28 MPa (HEC-CS) to 58.13 +/- 0.19 MPa (HEC-CS-LMP4), and elongation at break also declined. Incorporation of lemon peel powder enhanced antioxidant activity from 27.33 +/- 3.47% in the lowest LMP film to 55.31 +/- 0.65% in the highest while also improving antimicrobial properties. The 12-day packaging test on the blueberries showed that unwrapped blueberries lost 64.39 +/- 1.20% of the weight, whereas HEC-CS-LMP4 film lost only 16.09 +/- 0.12%. These findings support the use of this biomaterial in sustainable and bioactive packaging.
Keywords: biodegradable; chitosan; food packaging; hydroxyethyl cellulose; lemon peel